Effects of cluster vs. traditional sets complex training on physical performance adaptations of trained male volleyball players - Rong, B.; Xiu, C. (Journal of Sports Science & Medicine, 2024)
This study aimed to examine the impact of different set configurations during combination of resistance and plyometric training (complex [COX]) on jumping ability, power output, strength, and hormonal adaptations in young male volleyball players after a 6-week training period. A randomized controlled trial was conducted with twenty-four trained male volleyball players under the age of 19, who were assigned to one of two groups for lower-body COX training: cluster sets (CS-COX: n = 8) or traditional sets (TS-COX: n = 8), with an additional active control group (CON: n = 8). The players underwent evaluations for countermovement vertical jump (CMVJ), spike jump (SPJ), T-test change of direction speed (T-test CODS), one repetition maximum (1RM) in the back squat and leg press, and the Wingate Anaerobic Test before and after the 6-week training intervention (12 sessions in total). Blood samples were also collected before and after training to assess resting testosterone and cortisol responses. Following the training, both the CS-COX and TS-COX groups exhibited significantly greater (p = 0.001) changes than the CON group in the variables, while similar improvements in maximal strength, mean power output, and testosterone adaptations were observed following the training (p < 0.05). Moreover, the CS-COX group demonstrated greater improvements in CMVJ (effect size [ES] = 0.36), SPJ (ES = 0.06), T-test CODS (ES = -0.60), and peak power output (ES = 0.72), along with greater reductions in resting cortisol (ES = -0.30) levels compared to the TS-COX group after the 6-week intervention (p < 0.05). In conclusion, the results indicate that incorporating cluster sets during COX training sessions led to more favorable changes in bio-motor ability, peak power output, and cortisol adaptations, with greater consistency and uniformity in adaptations among the players compared to traditional set configurations.